Sex-dependent dominance at a single locus maintains variation in age at maturity in Atlantic salmon: a resolution for intra-locus sexual conflict? - Barson, Nicola B.; Aykanat, Tutku; Hindar, Kjetil; Baranski, Matthew; Bolstad, Geir H.; Fiske, Peder; Jacq, Celeste; Jensen, Arne J.; Johnston, Susan E.; Karlsson, Sten; Kent, Matthew; Moen, Thomas; et al.
2016